Sleeved WRe-TZM composite material and forging method thereof
Through the cover-type structure, the WRe layer is fitted in the concave space of the Mo cover and covered the TZM layer, which solves the problem of insufficient density of the WRe layer, and achieves the increase in density and the extension of the service life of the rotating anode target.
Patent Information
- Application Number
- CN202411719236.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
AI Technical Summary
The density of the WRe layer in the existing WRe-TZM composite materials is difficult to exceed 18.3 g/cm3, especially when the diameter of the rotary anode target exceeds 140 mm, it affects the service life.
Using a cover-type structure, the WRe layer is embedded in the cylindrical concave space of the Mo cover and covers the TZM layer through the combination of the Mo cover, the WRe layer is embedded in the cylindrical concave space of the Mo cover and covers the TZM layer, thereby increasing the density of the WRe layer through pressing, sintering and annealing forging processes.
When the diameter exceeds 140 mm, the density of the WRe layer exceeds 18.3 g/cm3 to 18.8 g/cm3, extending the service life of the rotating anode target and reducing the difficulty of forging deformation.
Smart Images

Figure CN119609142A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder metallurgy, and in particular to a sheathed WRe-TZM composite material and a forging method thereof. Background Art
[0002] CT (Computed Tomography), or electronic computer tomography, can perform non-invasive high-resolution imaging of the human body and clearly display the information of the lesions inside the human body. It has become an indispensable and important means of examination in modern medical diagnosis and modern social health care. The CT tube is the device that generates the X-ray source in the CT machine, which can be called the "core" of the CT. The rotating anode target, as the source of the X-ray of the CT tube, can be called the "heart" of the CT tube.
[0003] During the operation of the rotating anode target, the surface temperature of the tungsten-rhenium layer will change dramatically from room temperature to 2600℃ due to the bombardment of the electron beam. The surface of the tungsten-rhenium layer will gradually crack due to the impact of cold and heat, which will affect the service life. The service life of the tungsten-rhenium layer is closely related to the performance of the tungsten-rhenium layer itself, especially the density of the tungsten-rhenium layer. Generally speaking, the higher the density of the tungsten-rhenium layer, the longer the service life.
[0004] The WRe-TZM composite material of the rotating anode target is currently prepared by the following methods: ① Laying tungsten-rhenium powder in the mold; ② Laying TZM powder in the mold; ③ Pressing; ④ Sintering; ⑤ Forging. The tungsten-rhenium layer prepared by the above process has the problem of insufficient density, especially when the direct diameter of the rotating anode target exceeds 140 mm, the density of the tungsten-rhenium layer is difficult to exceed 18.3g / cm 3 It can be seen that how to further improve the density of the WRe layer in the WRe-TZM composite material is still a problem that needs to be solved by those skilled in the art. Summary of the invention
[0005] In order to solve the technical problem of how to further improve the density of the WRe layer in the WRe-TZM composite material, the present invention provides a sheath-type WRe-TZM composite material, comprising: a Mo sheath, a WRe layer and a TZM layer; Wherein, the Mo sheath is made by pressing Mo powder and has a cylindrical concave space, the WRe layer is embedded in the cylindrical concave space, and the top of the WRe layer is flush with the top of the Mo sheath periphery; The TZM layer covers the Mo sheath and the upper part of the WRe layer, and the periphery of the TZM layer is flush with the periphery of the Mo sheath; The WRe layer is made of tungsten-rhenium alloy, which is composed of W and Re; The TZM layer is made of a molybdenum-based alloy consisting of Ti, Zr, C, and Mo.
[0006] In one embodiment, the particle size of Mo in the Mo sheath is 0.5-100 μm.
[0007] In one embodiment, the weight percentages of the components of the tungsten-rhenium alloy are: W 85%-97%, Re 3%-15%.
[0008] In one embodiment, the components of the molybdenum-based alloy are as follows by weight: Ti 0.1%-1%, Zr 0.05%-0.2%, C 0.01%-0.2%, Mo 98.6%-99.84%.
[0009] The present invention also provides a forging method of the sheathed WRe-TZM composite material as described above, comprising the following steps: Assemble the bottom mold and the outer mold into a cylindrical mold; Spread Mo powder in a cylindrical mold; Using a convex upper die to perform pressing and holding pressure, a Mo sleeve having a cylindrical concave space is obtained; Laying WRe powder inside the cylindrical concave space of the Mo sheath; Spread another layer of TZM powder in the cylindrical mold; Use a flat upper die to perform pressing and pressure holding to obtain a composite material powder blank; The composite material powder blank is taken out from the mold, and placed in a hydrogen atmosphere for heat preservation and sintering to obtain a composite material sintered blank; The composite material sintered blank is annealed and forged to obtain the sheathed WRe-TZM composite material.
[0010] In one embodiment, the Mo powder is paved with a thickness of ≥1 mm.
[0011] In one embodiment, when the Mo powder is pressed and maintained under pressure using the convex upper die, the pressure is ≥20 MPa and the pressure maintenance time is ≥1 min.
[0012] In one embodiment, when a flat upper mold is used for pressing and holding pressure, the pressure is ≥100 MPa and the holding time is ≥1 min.
[0013] In one embodiment, the sintering temperature is ≥2000° C., and the sintering time is ≥3 h.
[0014] In one embodiment, the annealing forging temperature is ≥1500° C., and the forging pressure is ≥100 MPa.
[0015] The sheathed WRe-TZM composite material provided by the present invention comprises a Mo sheath, a WRe layer and a TZM layer, wherein the WRe layer is coated in the internal space formed by the Mo sheath and the TZM layer, and when the diameter of the sheathed WRe-TZM composite material exceeds 140 mm, the density of the tungsten-rhenium alloy in the WRe layer exceeds 18.3 g / cm 3 The technical bottleneck of the project was solved, and the highest density reached 18.8 g / cm 3 , making a rotating anode target can greatly extend its service life.
[0016] The present invention also provides a forging method for the sheath-type WRe-TZM composite material, which comprises pre-pressing a Mo sheath with a cylindrical concave space, laying WRe powder in the Mo sheath, and then covering it with TZM powder, and then pressing, sintering, and calcining to form a thermal insulation layer on the outside of the WRe layer, thereby reducing the deformation difficulty caused by the poor thermal insulation ability of the tungsten-rhenium alloy and the excessively fast temperature drop during the forging process. At the same time, due to the existence of the sheath structure, the stress mode of the WRe layer is changed, and its stress-strain mode is changed from deformation under unidirectional compressive stress to deformation under triaxial compressive stress, which synergizes with the thermal insulation effect of the sheath to improve the alloy density of the WRe layer after forging, breaking through 18.3 g / cm 3 This is a technical bottleneck.
[0017] In summary, compared with the prior art, the sheathed WRe-TZM composite material and the forging method thereof provided by the present invention slow down the temperature drop rate of the WRe layer through the sheath design, improve the stress-strain mode of the WRe layer, and reduce the difficulty of forging deformation of the WRe layer, thereby achieving an increase in the alloy density of the WRe layer and breaking through the technical bottleneck, and manufacturing it into a rotating anode target in a CT tube, effectively improving the service life of the rotating anode target. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 A schematic diagram of a sheathed WRe-TZM composite material provided in Example 1 of the present invention; Figure 2 A schematic diagram of a cylindrical mold provided in Example 1 of the present invention; Figure 3 A schematic diagram of laying Mo powder in a cylindrical mold provided in Example 1 of the present invention; Figure 4A schematic diagram of a pressed Mo sheath provided in Example 1 of the present invention; Figure 5 A schematic diagram of laying WRe powder in a Mo sheath provided in Example 1 of the present invention; Figure 6 A schematic diagram of laying TZM powder in a cylindrical mold provided in Example 1 of the present invention; Figure 7 Schematic diagram of the pressed and sheathed WRe-TZM composite material provided in Example 1 of the present invention.
[0020] Reference numerals: DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In the description of the present invention, it should be noted that the terms "upper", "lower", "inside", "outside", "middle", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they cannot be understood as limitations on the present invention.
[0023] The present invention provides the following embodiment to forge a sheathed WRe-TZM composite material, such as Figure 1 As shown, it includes: a Mo sheath 11, a WRe layer 12 and a TZM layer 13; The Mo sheath 11 is made by pressing Mo powder and has a cylindrical concave space, the WRe layer 12 is embedded in the cylindrical concave space, and the top of the WRe layer 12 is flush with the top of the periphery of the Mo sheath 11; The TZM layer 13 covers the upper part of the Mo sheath 11 and the WRe layer 12 , and the periphery of the TZM layer 13 is flush with the periphery of the Mo sheath 11 .
[0024] Example 1 refer to Figure 2 As shown, the bottom mold 21 and the outer mold 22 are assembled into a cylindrical mold 20; During specific use, the platform size of the bottom mold 21 is φ223 mm × 50 mm, and the overall size is φ400 mm × 70 mm. The inner diameter size of the outer mold 22 is φ223 mm × 150 mm, and the overall size is φ400 mm × 150 mm.
[0025] refer to Figure 3 As shown, Mo powder is spread in a cylindrical mold 20; In the specific operation, the Mo powder was paved with a thickness of 1 mm, a particle size of 1 μm, and a paved weight of 160 g.
[0026] refer to Figure 4 As shown, the convex upper mold 23 is used for pressing and holding pressure to obtain the Mo sheath 11 having a cylindrical concave space; During the specific operation, the convex surface size of the convex upper mold 23 is φ220 mm × 2 mm, the overall size is φ223 mm × 100 mm, and the pressure is maintained at 20 MPa for 1 min.
[0027] refer to Figure 5 As shown, WRe powder is laid inside the cylindrical concave space of the Mo sheath 11; During the specific operation, the weight of WRe powder was 320 g.
[0028] refer to Figure 6 As shown, another layer of TZM powder is laid in the cylindrical mold 20; During the specific operation, the weight of TZM powder was 2300 g.
[0029] refer to Figure 7 As shown, a planar upper mold 24 is used for pressing and holding pressure to obtain a composite material powder blank; During the specific operation, the overall size of the planar upper mold 24 is φ223 mm × 100 mm, and the pressure is maintained at 100 MPa for 1 min.
[0030] The composite material powder blank is taken out from the mold, and placed in a hydrogen atmosphere for heat preservation and sintering to obtain a composite material sintered blank; In the specific operation, the sintering temperature is 2000℃ and the sintering is kept at this temperature for 3 hours.
[0031] The composite material sintered blank is annealed and forged to obtain the sheathed WRe-TZM composite material; During the specific operation, the annealing forging temperature is 1500°C and the forging pressure is 100 MPa.
[0032] Example 2 Assemble the bottom mold 21 and the outer mold 22 into a cylindrical mold 20; During specific use, the platform size of the bottom mold 21 is φ235 mm × 50 mm, and the overall size is φ400 mm × 70 mm. The inner diameter size of the outer mold 22 is φ235 mm × 150 mm, and the overall size is φ400 mm × 150 mm.
[0033] Spread Mo powder in a cylindrical mold 20; In the specific operation, the Mo powder was paved with a thickness of 5 mm, a particle size of 50 μm, and a paved weight of 800 g.
[0034] The convex upper mold 23 is used to perform pressing and holding pressure to obtain a Mo sheath 11 having a cylindrical concave space; During the specific operation, the convex surface size of the convex upper mold 23 is φ220 mm × 2 mm, the overall size is φ235 mm × 100 mm, and the pressure is maintained at 50 MPa for 10 minutes.
[0035] Laying WRe powder inside the cylindrical concave space of the Mo sheath 11; During the specific operation, the weight of WRe powder was 320 g.
[0036] Another layer of TZM powder is spread in the cylindrical mold 20; During the specific operation, the weight of TZM powder was 2300 g.
[0037] Using the flat upper mold 24 to perform pressing and holding pressure, a composite material powder blank is obtained; During the specific operation, the overall size of the planar upper mold 24 is φ235 mm × 100 mm, and the pressure is maintained at 200 MPa for 10 minutes.
[0038] The composite material powder blank is taken out from the mold, and placed in a hydrogen atmosphere for heat preservation and sintering to obtain a composite material sintered blank; In the specific operation, the sintering temperature is 2500℃ and the sintering is kept at this temperature for 10 hours.
[0039] The composite material sintered blank is annealed and forged to obtain the sheathed WRe-TZM composite material; During the specific operation, the annealing forging temperature is 1800°C and the forging pressure is 200 MPa.
[0040] Example 3 Assemble the bottom mold 21 and the outer mold 22 into a cylindrical mold 20; During specific use, the platform size of the bottom mold 21 is φ229 mm × 50 mm, and the overall size is φ400 mm × 70 mm. The inner diameter size of the outer mold 22 is φ229 mm × 150 mm, and the overall size is φ400 mm × 150 mm.
[0041] Spread Mo powder in a cylindrical mold 20; In the specific operation, the Mo powder was paved with a thickness of 3 mm, a particle size of 10 μm, and a paved weight of 480 g.
[0042] The convex upper mold 23 is used to perform pressing and holding pressure to obtain a Mo sheath 11 having a cylindrical concave space; During the specific operation, the convex surface size of the convex upper mold 23 is φ220 mm × 2 mm, the overall size is φ229 mm × 100 mm, and the pressure is maintained at 30 MPa for 5 minutes.
[0043] Laying WRe powder inside the cylindrical concave space of the Mo sheath 11; During the specific operation, the weight of WRe powder was 320 g.
[0044] Another layer of TZM powder is spread in the cylindrical mold 20; During the specific operation, the weight of TZM powder was 2300 g.
[0045] Using the flat upper mold 24 to perform pressing and holding pressure, a composite material powder blank is obtained; In specific operation, the overall size of the planar upper mold 24 is φ229 mm × 100 mm, and the pressure is maintained at 150 MPa for 5 minutes.
[0046] The composite material powder blank is taken out from the mold, and placed in a hydrogen atmosphere for heat preservation and sintering to obtain a composite material sintered blank; In the specific operation, the sintering temperature is 2200℃ and the sintering is kept at this temperature for 6 hours.
[0047] The composite material sintered blank is annealed and forged to obtain the sheathed WRe-TZM composite material; During the specific operation, the annealing forging temperature is 1600°C and the forging pressure is 150 MPa.
[0048] In Examples 1 to 3 of the present invention, specifically, the components in the WRe powder are as follows by weight: W 95%, Re 5%.
[0049] In Examples 1 to 3 of the present invention, specifically, the components in the TZM powder are as follows by weight: Ti 0.5%, Zr 0.1%, C 0.03%, and Mo 99.37%.
[0050] The present invention also provides a WRe-TZM composite material forged in the following comparative example: Comparative Example 1.1 The difference between this comparative example and Example 1 of the present invention is that there is no sheathing treatment. Specifically, the following steps are included: Assemble the bottom mold 21 and the outer mold 22 into a cylindrical mold 20, wherein the platform size of the bottom mold 21 is φ223 mm×50 mm, and the overall size is φ400 mm×70 mm, and the inner diameter size of the outer mold 22 is φ223 mm×150 mm, and the overall size is φ400 mm×150 mm; WRe powder was spread in a cylindrical mold 20, and then a layer of TZM powder was spread, and a flat upper mold 24 was used for pressing and holding pressure to obtain a composite powder blank, wherein the weight of the WRe powder was 320 g, the weight of the TZM powder was 2300 g, and the overall size of the flat upper mold 24 was φ223 mm × 100 mm, and the pressure was held at 100 MPa for 1 min; The composite material powder blank is taken out from the mold, placed in a hydrogen atmosphere and sintered at 2000° C. for 3 h to obtain a composite material sintered blank; The composite material sintered blank is annealed and forged at 1500° C. and 100 MPa to obtain the sheathed WRe-TZM composite material.
[0051] Comparative Example 1.2 The difference between this comparative example and Example 2 of the present invention is that there is no sheathing treatment. Specifically, the following steps are included: Assemble the bottom mold 21 and the outer mold 22 into a cylindrical mold 20, wherein the platform size of the bottom mold 21 is φ235 mm×50 mm, and the overall size is φ400 mm×70 mm, and the inner diameter size of the outer mold 22 is φ235 mm×150 mm, and the overall size is φ400 mm×150 mm; WRe powder was spread in a cylindrical mold 20, and then a layer of TZM powder was spread, and a flat upper mold 24 was used for pressing and holding pressure to obtain a composite powder blank, wherein the weight of the WRe powder was 320 g, the weight of the TZM powder was 2300 g, and the overall size of the flat upper mold 24 was φ235 mm × 100 mm, and the pressure was held at 200 MPa for 10 min; The composite material powder blank is taken out from the mold, placed in a hydrogen atmosphere and sintered at 2500° C. for 10 h to obtain a composite material sintered blank; The composite material sintered blank is annealed and forged at 1800° C. and 200 MPa to obtain the sheathed WRe-TZM composite material.
[0052] Comparative Example 1.3 The difference between this comparative example and Example 1 of the present invention is that there is no sheathing treatment. Specifically, the following steps are included: Assemble the bottom mold 21 and the outer mold 22 into a cylindrical mold 20, wherein the platform size of the bottom mold 21 is φ229 mm×50 mm, and the overall size is φ400 mm×70 mm, and the inner diameter size of the outer mold 22 is φ229 mm×150 mm, and the overall size is φ400 mm×150 mm; WRe powder was spread in a cylindrical mold 20, and then a layer of TZM powder was spread, and a flat upper mold 24 was used for pressing and holding pressure to obtain a composite powder blank, wherein the weight of the WRe powder was 320 g, the weight of the TZM powder was 2300 g, and the overall size of the flat upper mold 24 was φ229 mm × 100 mm, and the pressure was held at 150 MPa for 5 min; The composite material powder blank is taken out from the mold, placed in a hydrogen atmosphere and sintered at 2500° C. for 6 h to obtain a composite material sintered blank; The composite material sintered blank is annealed and forged at 1600° C. and 150 MPa to obtain the sheathed WRe-TZM composite material.
[0053] Comparative Example 2 The difference between this comparative example and Example 1 of the present invention is that the particle size of the Mo powder is 60 μm.
[0054] Comparative Example 3 The difference between this comparative example and Example 1 of the present invention is that the Mo powder laying thickness is 0.5 mm, the Mo powder laying weight is 80 g, the inner diameter size of the outer mold 22 is φ221.5 mm × 100 mm, and the overall size of the convex upper mold 23 and the flat upper mold 24 are both φ221.5 mm × 100 mm.
[0055] Comparative Example 4 The difference between this comparative example and Example 1 of the present invention is that the sintering temperature is 1900°C.
[0056] Comparative Example 5 The difference between this comparative example and Example 1 of the present invention is that the heat preservation sintering time is 2 h.
[0057] Comparative Example 6 The difference between this comparative example and Example 1 of the present invention is that the annealing and forging temperature is 1400°C.
[0058] Comparative Example 7 The difference between this comparative example and Example 1 of the present invention is that the forging pressure is 80 MPa.
[0059] For the sheathed WRe-TZM composite materials prepared in the above Examples 1 to 3 and the WRe-TZM composite materials prepared in the above Comparative Examples 1 to 7, the tungsten-rhenium alloy density of the WRe layer 12 was measured in accordance with GB / T 3850-2015 Density measurement method for dense sintered metal materials and cemented carbides. The measurement results are summarized in Table 1.
[0060] Table 1 Density of tungsten-rhenium alloy in WRe-TZM composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 7
[0061] According to the data in Table 1, the density of the tungsten-rhenium alloy in the sheathed WRe-TZM composite material provided in Example 1 of the present invention reaches 18.8 g / cm 3 , breaking through 18.3 g / cm 3 The WRe-TZM composite material provided in Comparative Example 1.1 has a density of only 18.1 g / cm 3 , failed to break through 18.3 g / cm 3 Similarly, the density of tungsten-rhenium alloy in Examples 2 and 3 is 18.4 g / cm 3 , 18.6 g / cm 3 , both exceeded 18.3 g / cm 3 The density of the tungsten-rhenium alloy in the comparative examples 1.2 and 1.3, which only differ in that they are not coated, is 17.8 g / cm 3 , 18.0 g / cm 3 , also failed to break through 18.3 g / cm 3 It can be seen that the Mo powder coating treatment provides physical insulation conditions, the temperature drop of the tungsten-rhenium alloy during the forging process is reduced, and the tungsten-rhenium alloy is subjected to three-way compressive stress during forging, which reduces the difficulty of deformation and helps to further improve the density of the tungsten-rhenium alloy.
[0062] Furthermore, the comparative examples 2 to 7 are different from the example 1 in terms of Mo powder particle size, Mo powder laying thickness, sintering temperature, heat preservation sintering time, annealing forging temperature, and forging pressure. Although the density of the tungsten-rhenium alloy in the comparative examples 2 to 7 is improved, it fails to exceed 18.3 g / cm 3This technical bottleneck shows that the above process parameters also have an impact on the density performance of tungsten-rhenium alloy in the sheathed WRe-TZM composite material.
[0063] Although the terms such as encapsulation, compression, temperature drop, etc. are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional restrictions is contrary to the spirit of the present invention.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sheathed WRe-TZM composite material, characterized in that: include: Mo sheath (11), WRe layer (12) and TZM layer (13); The Mo sheath (11) is made by pressing Mo powder and has a cylindrical concave space, the WRe layer (12) is embedded in the cylindrical concave space, and the top of the WRe layer (12) is flush with the top of the peripheral edge of the Mo sheath (11); The TZM layer (13) covers the upper part of the Mo sheath (11) and the WRe layer (12), and the periphery of the TZM layer (13) is flush with the periphery of the Mo sheath (11); The WRe layer (12) is made of a tungsten-rhenium alloy consisting of W and Re; The TZM layer (13) is made of a molybdenum-based alloy consisting of Ti, Zr, C, and Mo.
2. The sheathed WRe-TZM composite material according to claim 1, characterized in that: The particle size of Mo in the Mo sheath (11) is 0.5-100 μm.
3. The sheathed WRe-TZM composite material according to claim 1, characterized in that: The components of the tungsten-rhenium alloy are as follows by weight: W 85%-97%, Re 3%-15%.
4. The encapsulated WRe-TZM composite material according to claim 1, characterized in that: The components of the molybdenum-based alloy are as follows by weight percentage: Ti 0.1%-1%, Zr 0.05%-0.2%, C 0.01%-0.2%, and Mo 98.6%-99.84%.
5. A forging method of the sheathed WRe-TZM composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Assembling the bottom mold (21) and the outer mold (22) into a cylindrical mold (20); Spreading Mo powder in a cylindrical mold (20); Using a convex upper die (23) to perform pressing and pressure holding, thereby obtaining a Mo sheath (11) having a cylindrical concave space; Laying WRe powder inside the cylindrical concave space of the Mo sheath (11); Spread another layer of TZM powder in the cylindrical mold (20); Using a flat upper mold (24) to perform pressing and pressure holding to obtain a composite material powder blank; The composite material powder blank is taken out from the mold, and placed in a hydrogen atmosphere for heat preservation and sintering to obtain a composite material sintered blank; The composite material sintered blank is annealed and forged to obtain the sheathed WRe-TZM composite material.
6. The forging method of the sheathed WRe-TZM composite material according to claim 5, characterized in that: The Mo powder is paved with a thickness of ≥1 mm.
7. The forging method of the sheathed WRe-TZM composite material according to claim 5, characterized in that: When the Mo powder is pressed and held under pressure using the convex upper die (23), the pressure is ≥20 MPa and the holding time is ≥1 min.
8. The forging method of the encapsulated WRe-TZM composite material according to claim 5, characterized in that: When the flat upper die (24) is used for pressing and holding pressure, the pressure is ≥100 MPa and the holding time is ≥1 min.
9. The forging method of the encapsulated WRe-TZM composite material according to claim 5, characterized in that: The sintering temperature is ≥2000℃ and the sintering time is ≥3 h.
10. The forging method of the encapsulated WRe-TZM composite material according to claim 5, characterized in that: Annealing forging temperature ≥1500℃, forging pressure ≥100 MPa.